Comparación del alimento peletizado y alimento no peletizado en el rendimiento de cerdos en la etapa de crecimiento en Zúngaro Cocha, 2023 - Panduro Ruiz, Gian Carlos (2024)
This study focuses on comparing the productive performance of pigs in the growth stage, using pelleted and non-pelleted feed, in Zúngarococha during the year 2023. The overall objective was to evaluate and compare the performance of pigs fed these two types of feed. A pure and cross-sectional experimental design was used, through hypothesis testing of two independent samples and regression analysis, with a sample of 32 randomly selected pigs, between males and females. Data was collected through production records and scales, stored in Excel. The results revealed significant differences in performance between the two groups of pigs, with better results in growth, feed conversion and feed efficiency in pigs fed pelleted feed. These findings are relevant to producers, researchers and other actors in the pig industry, providing valuable information for decision-making regarding the feeding and management of growing pigs.